Finite elements method-based ICRF wave heating simulation integrating with SOL plasma for EAST tokamak - Zhang, J.H.; Zhang, X.J.; Qin, C.M. (Nuclear fusion, 2022)
Ion cyclotron range of frequency (ICRF) wave heating simulation is often carried out in the core plasma region. However, the inclusion of scrape-off layer (SOL) plasma in the simulation model may lead to a new physical phenomenon and needs to be studied. In this paper, we apply a finite elements method based on the approach of Vallejos et al (2019 Nucl. Fusion 59 076022), to simulate ICRF wave heating to account realistically for SOL plasma of the EAST. In the presence of the density pedestal near the last closed flux surface, a kind of cavity mode is observed for the case of low parallel wave number. Near the ion–ion hybrid resonance (IIR) layer in the SOL region, mode conversion from fast waves to slow waves takes place. ICRF wave coupling characteristics are roughly consistent with the prediction of the dispersion relation except for some small deviations, which may be caused by fast wave reflection in the high-field side. Approximately on-axis heating of H ion is observed and the power deposition zone broadens with parallel wave number increasing. Wave energy dissipation in SOL plasma is less than 7% and localized near the IIR region. Furthermore, the comparison between D(H) and D(He-3) minority heating scenarios is also carried out. The results and conclusions in this paper can provide a theoretical reference for ICRF heating experiments and may supply a new insight into the form of ICRF waves in the plasma edge.